INTEGRATED RENEWAL PROCESS - Suyono .; J.A.M. van der Weide (Journal of the Indonesian Mathematical Society, 2007)
The marginal distribution of integrated renewal process is derived in this paper. Our approach is based on the theory of point processes, especially Poisson point processes. The results are presented in the form of Laplace transforms. DOI : http://dx.doi.org/10.22342/jims.13.2.64.149-159